Digital twins in the build environment : fundamentals, principles and applications - Lu, Qiuchen; Xie, Xiang; Parlikad, Ajith; Schooling, J. M. (Jennifer M.); Pitt, Michael (ICE Publishing, 2022)
This volume offers a new, comprehensive, systematic and clear view of digital twin development in the architecture, engineering, construction and facilities management sectors. It will help you to uncover the implementation and development of digital twins work and understand how to operate and maintain digital twin assets, buildings and cities. Using a structured approach, the book explains how to create and use digital twins effectively including principles, system architecture, data structure and creation methods for the five layers needed (data acquisition, data transmission, digital model, data/model integration, and services). This is underpinned with real life cases studies of digital twin implementation at asset, building and city levels, revealing every angle that a digital twin can take.